EMPOWERMENT OF CREATIVE INDUSTRY BASED E-COMMERCE IN THE REGIONAL GOVERNMENT OF ENREKANG DISTRICT - Mutmainnah, Inayatul; Ramadani, Eka Fitra (Multifinance, 2023)
This research aims to find out how to empower creative industry-based e-commerce in local governments in Enrekang district. This research uses a qualitative method with a descriptive method in the form of observation. Data collection techniques were carried out using observation, interview, and documentation techniques. The reference for this research determines informants using purposive sampling techniques. The focus of this research is the efforts and strategies of MSME owners and the Enrekang district government in empowering creative industry-based e-commerce to increase creative industry income in the melona baba dairy cattle group. In this research, the research target is collaboration between the local government and the MSME owners of the Melona Baba dairy cattle group in empowering e-commerce. The results of this research show that the regional government has facilitated the procurement of dairy cows, food, and budgets for other needs in developing MSMEs. In terms of e-commerce empowerment itself, it has been implemented by the Melona Baba dairy cattle group as the only dairy cattle MSME that utilizes digitalization in the development of its MSMEs, but cooperation in e-commerce empowerment has not yet been developed with the Enrekang district government. The results of the interview research indicate that there is a need for direct involvement from local governments in increasing understanding of empowering e-commerce based on creative industries.